SUPORTE SOCIAL E AUTOEFICÁCIA EM IDOSOS - Bertoldo, Dilma Medeiros (2012)
The issues of human development since ancient times are of interest in the various areas of knowledge. In view of the increase in life expectancy, the issues related to the aging process have gained importance, especially in relation to health policies. Health is a central concern in the field of aging, since health problems can lead to several problems for the elderly and their families. This study aimed to seek to identify the associations between perceptions of self-efficacy and social support in elderly. Social support and self-efficacy are variables studied in different contexts. Studies show that both are able to collaborate to protect and promote health. Social support refers to the group of information that takes the individual to believe that he/she is praised, loved and cherished and it does feel belonging to a social network of reciprocal communication. Self-efficacy can be defined as the set of beliefs that the individual has about their abilities to organize and perform actions to fulfil specific tasks. Therefore, identifying the existence of associations between the perceptions of social support and self-efficacy can contribute to give greater strength to the existing knowledge on these themes and on the aging process. Participated in this study 61 elderly of both sexes, with an average age of 67 years, with degree of schooling that ranged from elementary school to graduation and participants in health promotion actions. All were volunteers and authorized their participation through signing a consent form. Data collection was made upon the application of a questionnaire containing scales to evaluate the constructs, as well as issues for characterization of participants. The data were analyzed electronically through the calculation of frequencies, percentage, averages and standard deviations. To test the hypothesis, was calculated the correlation (Pearson r) among the variables of study. Among the obtained results, the perception of social support, both in the emotional dimension and practical dimension to the elderly participants in this study, is that "many times" are loved, cherished and praised and that belong to a network of communication and mutual obligations. In the case of perception of self-efficacy, it was found that these participants have beliefs that "sometimes it is true" that are effective and which are able to organize and perform actions to fulfill specific tasks. Points out that there are no significant correlations between perception of social support and self-efficacy, i.e. the levels of perception of social support do not vary in proportion to the variation of the beliefs of self-efficacy in elderly. This means that for these participants, would not be effective to invest in improvements of social support, since this would not have an impact on their self-efficacy beliefs. The realization of new research with older non-participants of health promotion actions, because they may think that the elderly are not engaged in these kinds of actions might need greater social support and thus have their self-efficacy beliefs associated with their perception of social support.